“Don't sweep the floor!” Verbal and nonverbal taboo in Nagan Raya, Aceh - Veni Nella Syahputri; Meta Keumala; Endah Anisa Rahma; Zahratul Idami; Edy Saputra (Studies in English Language and Education, 2019)
In daily life, individuals occasionally use language to connect with other individuals, and they have their specific manner to pick the language variety which can affirm their character. This language can be in the form of verbal and nonverbal language. This research aimed at finding out the types of verbal and non-verbal taboo, along with the mythical and factual reasons underlying their usage. The method used was qualitatively based. The data collection was done through several interviews with the participants who are the native speakers of Acehnese in Nagan Raya. Later on, the data were recorded using an android device and in the analysis, the three-step analysis was employed. The process was data reduction, data display, and data verification. Then the results show that, first, nine swearing taboo words are occasionally used by the people there. The reason for using these words is generally to express anger and disappointment. Second, concerning the non-verbal taboo, there were 10 data obtained concerning non-verbal taboo, and the reason behind using these nonverbal taboo is to threat the youth to get them obedient so that they can carry out the day safely.